Efeito da concentração de parafina na formação de hidratos de metano em emulsões de agua em óleo mineral - Melhorim, Guilherme Rainho (2022)
The ow of oil through the pipes generates high mixing rates due to the intense shocks on the walls of these pipes. In addition, at the bottom of the ocean there is a combination of two factors: high pressures and low temperatures. These particu larities represent the main causes of hydrate nucleation, which is a solid compound where low molecular weight molecules are encapsulated by water molecules. The for mation of hydrates triggers a series of problems in the oil industry, which can block the ow of oil and cause production losses. There are large areas of importance involving hydrates, from climate change concerns to the development of sustainable technologies. A third application of hydrates concerns ow assurance, vital for the oil and gas industry. It is in this area that we will focus our studies. For this, the formation of methane hydrates is investigated using water-in-mineral oil emulsions at high pressures and low temperatures. Span80 surfactant is used to stabilize the emulsions. Initially, some parameters are varied to observe their e ects: shear rate, cooling temperature and average droplet diameter. Finally, the e ect of the paraf n concentration on the formation of hydrates is analyzed. For this, a rotational rheometer and a pressure cell are used to simulate a pressurized environment.